Sulfide solid electrolyte and preparation method thereof, battery and application

By optimizing the preparation method of sulfide solid electrolytes and controlling the particle size of raw materials and sintering process, the problems of brittle fracture and insufficient ionic conductivity of sulfide solid electrolytes during machining have been solved, resulting in electrolyte materials with high fracture toughness and high ionic conductivity, which are suitable for high energy density batteries and electric vertical takeoff and landing aircraft.

CN120767395BActive Publication Date: 2025-11-04GUANGZHOU TINCI MATERIALS TECH

Patent Information

Application Number
CN202511281559.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-11-04
Estimated Expiration
2045-09-09

AI Technical Summary

Technical Problem

Existing sulfide solid electrolytes are prone to brittle fracture during machining and have insufficient ionic conductivity, making it difficult to meet the safety and structural stability requirements of high-energy-density batteries.

Method used

By using compounds with the chemical formula Li7-APS6-AXA or Li7-APS6-AXA composites doped with other elements, the preparation method of sulfide solid electrolytes is optimized by controlling the particle size of raw materials, the amount of solvent used, and the multi-step sintering process, thereby improving their fracture toughness and ionic conductivity.

Benefits of technology

Stable control of the fracture toughness of sulfide solid electrolytes within the range of 0.5-2 MPa m1/2 was achieved, improving mechanical integrity and electrochemical performance, ensuring the structural stability and ionic conductivity of the battery, and making it suitable for electric vertical takeoff and landing aircraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120767395B_ABST
    Figure CN120767395B_ABST
Patent Text Reader

Abstract

The application relates to the field of electrochemistry, and provides a sulfide solid electrolyte, a preparation method thereof, a battery and an application. 7‑ A PS 6‑A X A The application also provides a sulfide solid electrolyte selected from any one of compounds of a chemical formula Li 7‑ A PS 6‑A X A X is halogen, and 1<=A<=2; wherein the sulfide solid electrolyte has a fracture toughness of 0.5-2 MPa m 1 / 2 The sulfide solid electrolyte has high fracture toughness and ionic conductivity. Further, the preparation method controls the particle size of a substrate, reduces the solvent consumption and optimizes the sintering step, thereby improving the fracture toughness, high purity and high ionic conductivity of the product, and significantly reducing environmental pollution, energy consumption and production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemical technology, and in particular to a sulfide solid electrolyte and its preparation method, a battery containing the sulfide solid electrolyte, and the application of the battery. Background Technology

[0002] Solid-state electrolytes (SPECs) are key materials for future high-energy-density batteries, significantly improving battery safety and overall performance. In recent years, with the development of new energy electric vehicles and energy storage technologies, the demand for high-performance SPECs has been increasing, driving continuous progress in related research and technologies. Currently, sulfide SPECs have become a research hotspot due to their excellent ionic conductivity and electrochemical stability. However, the widely studied silver-germanium sulfide SPECs (LPSCs) generally suffer from poor mechanical properties and brittleness, especially during machining processes such as electrode pressing and battery assembly, where cracking and spalling are common, severely restricting their engineering applications. Furthermore, during charge and discharge, the electrolyte is prone to brittle fracture due to the influence of lithium dendrites, failing to meet the structural stability and safety requirements of solid-state batteries. Therefore, controlling the fracture toughness of sulfide SPECs has become crucial for improving their overall performance and practicality.

[0003] In the prior art, the fracture toughness of solid electrolytes can be improved by adding high-toughness substances. However, the addition of high-toughness substances may lead to a decrease in the ionic conductivity of sulfide solid electrolytes. Therefore, how to balance the fracture toughness and ionic conductivity of solid electrolytes has become an urgent technical problem to be solved. Summary of the Invention

[0004] The purpose of this application is to provide a sulfide solid electrolyte, its preparation method, a battery protecting the sulfide solid electrolyte, and the application of the battery, so as to improve the fracture toughness and ionic conductivity of the sulfide solid electrolyte, thereby developing a safer and more efficient battery. The specific technical solution is as follows:

[0005] The first aspect of this application provides a sulfide solid electrolyte selected from the chemical formula Li 7-A PS 6-A X A Compounds and Li coated or doped with other elements 7-A PS 6-A X A Any of the compounds, where X is a halogen, 1 ≤ A ≤ 2; wherein the fracture toughness of the sulfide solid electrolyte is 0.5-2 MPa m. 1 / 2 .

[0006] In some embodiments of this application, the cell parameters of the sulfide solid electrolyte are a=b=c=9.84~9.90Å.

[0007] In some embodiments of this application, the sulfide solid electrolyte has an ionic conductivity ≥ 5.5 mS / cm.

[0008] In some embodiments of this application, the other elements are selected from at least one of the elements O, Se, F, Mg, Ca, Sr, Zn, Sc, Sb, Si, Ge, Sn, B, Al, Ga, In, Ti, Zr, V, Nb, Cu, Ni, Mn, Cr, Ag, La, Ce, Tb, Te, Pb, As, Bi, Fe, Mo, and Co.

[0009] In some embodiments of this application, the sulfide solid electrolyte is selected from Li doped with other elements. 7- A PS 6-A X A The complex, wherein the other elements doped are introduced from oxides selected from at least one of MgO, CaO, V2O5, MnO2, Fe2O3, CoO, NiO, CuO, ZnO, ZrO2, MoO3, Ag2O, SrO, TiO2, Cr2O3, CeO2, and PbO.

[0010] The second aspect of this application provides a chemical formula of Li provided in the first aspect of this application. 7-A PS 6-A X A The method for preparing the compound includes:

[0011] Under an inert atmosphere, the substrate and solvent are mixed and mechanically stirred to obtain a suspension; wherein the substrate includes Li2S, P2S5 and LiX, where X is a halogen; before mixing the substrate and solvent, the substrate is pulverized to a particle size of 3µm < D50 < 30µm, 40µm < D99 < 80µm; preferably 8µm < D50 < 20µm, 50µm < D99 < 65µm;

[0012] The molar ratio of Li2S to P2S5 is (3~5):1; the molar ratio of P2S5 to LiX is 1:(2~4); the mass ratio of the substrate to the solvent is 1:(2~4).

[0013] The suspension was allowed to stand at room temperature and pressure to allow the solvent to evaporate, yielding Li. 7-A PS 6-A X A Precursor mixture;

[0014] The Li7-A PS 6-A X A The precursor mixture was sintered to obtain Li 7-A PS 6-A X A The sintering process includes a first sintering and a second sintering. The temperature of the first sintering is 150~300℃ and the time is 1~6h. The temperature of the second sintering is 450~600℃ and the time is 5~10h.

[0015] In some embodiments of this application, the substrate is pulverized to a particle size of 8 μm < D50 < 20 μm and 50 μm < D99 < 65 μm before being mixed with the solvent.

[0016] In some embodiments of this application, the temperature of the first sintering is 150~200℃ and the time is 3~6h; the temperature of the second sintering is 550~600℃ and the time is 5~7h.

[0017] In some embodiments of this application, the heating rate of the first sintering is 2~7℃ / min; the heating rate of the second sintering is 5~12℃ / min.

[0018] In some embodiments of this application, the solvent is selected from at least one of n-hexane, benzene, toluene, cyclohexane, n-pentane, cyclopentane, n-heptane, and dimethyl carbonate.

[0019] In some embodiments of this application, the mechanical stirring is carried out at room temperature and pressure, the mechanical stirring speed is 300 rpm to 600 rpm, and the mechanical stirring time is 12 to 24 hours.

[0020] In some embodiments of this application, the solvent evaporation rate is 1.5~7.0 mg / cm³. 2 ·h.

[0021] In some embodiments of this application, post-processing is required after sintering, including pulverization.

[0022] A third aspect of this application provides a battery comprising a positive electrode, a negative electrode, and a sulfide solid electrolyte as described in the first aspect of this application.

[0023] The fourth aspect of this application provides the application of the battery described in the third aspect of this application in an electric vertical takeoff and landing aircraft.

[0024] The beneficial effects of this application are:

[0025] This application provides a sulfide solid electrolyte, its preparation method, battery, and application. The solid electrolyte is selected from the chemical formula Li.7-A PS 6-A X A Compounds and Li coated or doped with other elements 7-A PS 6-A X A Any of the compounds, where X is a halogen, 1 ≤ A ≤ 2; wherein the fracture toughness of the sulfide solid electrolyte is 0.5-2 MPa m. 1 / 2 This application achieves controllable adjustment of fracture toughness by optimizing the synthesis process of sulfide solid electrolytes, ensuring that the fracture toughness of the final product is stably controlled within 0.5–2 MPa·m. 1 / 2 Within the ideal range, the mechanical integrity and structural stability of sulfide solid electrolytes are improved during actual processing and application. The fracture toughness of the sulfide solid electrolyte within the scope of this application not only effectively prevents crack propagation and fragmentation during mechanical operations such as pressing, cutting, and assembly, improving the sheet yield and efficiency of the electrolyte, but also maintains sufficient density and interfacial adhesion, helping to reduce interfacial impedance and improve overall battery performance. Compared to materials obtained by traditional synthesis methods, which have lower fracture toughness (<0.5 MPa·m...), this method... 1 / 2 ) or too high (>2.0 MPa·m 1 / 2 The sulfide solid electrolyte obtained in this application exhibits good comprehensive mechanical properties and electrochemical compatibility, which avoids the processing brittleness or forming difficulties caused by the sulfide solid electrolyte.

[0026] Simultaneously, this application achieves the synthesis of sulfide solid electrolytes with high mechanical properties while also endowing them with high electrochemical performance through process design. The particle size control strategy ensures more complete reaction and more uniform crystal growth, thereby helping to stabilize the crystal structure of the target product and maintain its cell parameters within the ideal range of 9.84–9.90 Å. The cell parameters of the sulfide electrolyte directly affect the geometry of its ion migration channels. Appropriate cell expansion (9.84–9.90 Å) can adjust the lithium-ion channel width and migration barrier, facilitating the realization of continuous three-dimensional lithium-ion migration paths, thus endowing the material with high room-temperature ionic conductivity (≥5.5 mS / cm). Therefore, this application not only enhances mechanical properties but also improves electrochemical performance, providing a new preparation approach for solid electrolyte materials that simultaneously pursue high fracture toughness and high conductivity in practical applications.

[0027] Furthermore, the preparation method of this application improves the dispersion uniformity and reactivity of the substrate by separately pulverizing the substrate and controlling its D50 and D90, thereby optimizing the fracture properties of the sulfide solid electrolyte. By reducing the amount of solvent used, the mass ratio of solvent to substrate is reduced to (2~4):1, reducing the organic waste gas emissions and solvent treatment burden during the production process. Moreover, by reducing the amount of solvent used, the drying step does not require vacuum drying but can be completed by standing at room temperature and pressure, which not only reduces energy consumption but also lowers production costs. At the same time, the merging of the drying and sintering processes further simplifies the process flow and improves production efficiency. In addition, the multi-step sintering method used in this application helps to reduce the residual organic solvent in the electrolyte and alleviates the carbonization phenomenon that may occur during subsequent sintering. By controlling the sintering temperature and time within the range of this application, the purity and uniformity of the electrolyte powder are improved. Furthermore, batteries containing the sulfide solid electrolyte of this application or the sulfide solid electrolyte prepared by the preparation method of this application have high safety and energy density as well as good low-temperature performance, and can be applied to electric vertical take-off and landing aircraft, such as low-altitude economical manned electric vertical take-off and landing aircraft.

[0028] Furthermore, controlling the molar ratio of the substrate, the mass ratio of the substrate to the solvent, the second sintering temperature, the second sintering time, and the second sintering heating rate within the scope of this application also has the following effects:

[0029] Substrate molar ratio: Adjusting the halogen doping amount in the substrate within the range specified in this application (e.g., the molar ratio of Li2S:P2S5 is (3~5):1, and the molar ratio of P2S5:LiX is 1:(2~4)) helps to form a stable crystal structure, improves grain boundary bonding, and enhances the overall fracture toughness of the material by strengthening the densification process between grains. When the lithium halide doping amount is too low, the effect is not obvious, while excessive lithium halide may lead to the enrichment of unreacted secondary phases such as LiCl, forming brittle inclusions, which become the initiation source of microcracks and are also detrimental to the improvement of mechanical properties.

[0030] Substrate to solvent mass ratio: Using inert solvents within the scope of this application (such as n-hexane and toluene) not only helps to fully disperse and mix the substrate particles, but also suppresses side reactions between reaction precursors, thereby obtaining precursor powders with uniform particles and dense structure. In addition, when the mass ratio of substrate to solvent is controlled at (2~4):1, the system has good fluidity and dispersibility, which is conducive to the formation of dense microstructures during drying and sintering, thereby improving fracture toughness. Conversely, if the amount of solvent is insufficient, the raw material distribution will be uneven, which can easily lead to agglomeration, pores and microcracks; while excessive solvent may cause incomplete drying, which can lead to the formation of residual carbon sources or pores during sintering. These structural defects will become weak paths for crack propagation, significantly reducing the crack resistance of the material.

[0031] Secondary sintering temperature: An appropriate sintering temperature (450-600°C) helps promote intergranular bonding and the formation of sintering necks, thereby improving the material's density and reducing porosity. This results in a more uniform stress distribution, which is beneficial for inhibiting crack propagation and thus improving fracture toughness. However, if the sintering temperature is too low (e.g., below 450°C), it is difficult to achieve grain boundary bonding, resulting in numerous micropore defects inside the sample and increased brittleness. On the other hand, if the temperature is too high (e.g., above 600°C), it may cause abnormal grain growth, weakening of grain boundaries, and even volatilization of sulfur or halogen components, thereby destroying the overall structure of the material and reducing its mechanical stability.

[0032] Second sintering time: Short sintering time may lead to insufficient sintering, leaving open pores inside the material and reducing its crack resistance; while a reasonable sintering time (5-10 hours) helps grain growth and grain boundary diffusion, improving structural uniformity and toughness. However, if the sintering time is too long, it can easily induce grain coarsening and phase separation, which can lead to microcracks or reduce interfacial bonding.

[0033] Second sintering heating rate: Controlling the heating rate within a suitable range (5~12℃ / min) can suppress structural distortion, promote orderly grain growth and densification, thereby improving the fracture toughness of the material. Excessive heating can lead to temperature gradients within the material, accumulating thermal stress and inducing crack defects, which is detrimental to maintaining fracture toughness.

[0034] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time. Attached Figure Description

[0035] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these accompanying drawings.

[0036] Figure 1 The sulfide solid electrolyte (Li) prepared in Example 1-1 5.5 PS 4.5 Cl 1.5 X-ray diffraction pattern of )

[0037] Figure 2 The sulfide solid electrolytes (Li) prepared in Examples 1-15 5.5 PS 4.5 Cl 1.5 X-ray diffraction pattern of )

[0038] Figure 3The sulfide solid electrolyte (Li) prepared for Comparative Example 1-1 6.5 PS 5.5 Cl 0.5 X-ray diffraction pattern of )

[0039] Figure 4 The X-ray diffraction pattern of the solid electrolyte precursor mixture of Example 1-1;

[0040] Figure 5 The X-ray diffraction pattern of the solid electrolyte precursor mixture in Comparative Example 2-1 is shown.

[0041] Figure 6 The X-ray diffraction pattern of the solid electrolyte precursor mixture in Comparative Example 2-2 is shown.

[0042] Figure 7 The X-ray diffraction pattern of the electrolyte precursor powder in Comparative Example 3-2 is shown. Detailed Implementation

[0043] The technical solutions of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.

[0044] Existing technologies largely focus on improving ionic conductivity or enhancing air stability, with limited attention paid to systematically optimizing the mechanical and electrochemical properties of sulfide solid electrolytes from the perspective of material structure control. Particularly regarding fracture toughness, there is a lack of systematic research on designing synthetic methods to achieve target toughness ranges. Excessively low fracture toughness leads to brittleness during material processing, while excessively high toughness may cause over-plasticization, affecting density and interfacial contact. Therefore, developing a synthetic strategy for controllably adjusting fracture toughness to obtain sulfide solid electrolytes with both excellent fracture toughness and ionic conductivity is a pressing technical problem that needs to be solved.

[0045] Based on this, the first aspect of this application provides a sulfide solid electrolyte, which is selected from the chemical formula Li 7- A PS 6-A X A Compounds and Li coated or doped with other elements 7-A PS 6-A X A Any of the compounds, where X is a halogen, 1 ≤ A ≤ 2, the fracture toughness of the sulfide solid electrolyte is 0.5-2 MPa m. 1 / 2 .

[0046] Fracture toughness measures a material's ability to resist fracture in the presence of a crack. It is commonly represented by the symbol KIC and reflects the critical stress intensity factor required for crack propagation under stress. The unit is MPa·m. 1 / 2 Higher fracture toughness means that the material can withstand greater stress without fracturing even when defects or cracks are present.

[0047] The inventors discovered through research that maintaining the fracture toughness of sulfide solid electrolytes within 0.5–2 MPa·m 1 / 2 Within this range, sulfide solid electrolytes can effectively resist crack propagation caused by external forces, improve their structural integrity during battery assembly and cycling, prevent pulverization and failure, and resist lithium dendrite formation; at the same time, moderate fracture toughness can also retain a certain degree of deformation capacity, which helps to improve interface compatibility and reduce interface impedance. When the fracture toughness is below 0.5 MPa·m... 1 / 2 At this stage, sulfide solid electrolytes are too fragile and prone to decomposition under compression, cyclic expansion, or thermal stress, leading to interface contact degradation and an increased risk of battery short circuits; while when the fracture toughness exceeds 2 MPa·m 1 / 2 When sulfide solid electrolytes exhibit excessive plasticity, it may lead to increased grain boundary slip, structural disorder, or even induce the collapse of ion migration channels, thereby weakening ionic conductivity and increasing grain boundary impedance.

[0048] In this application, the doping methods described above include, but are not limited to, introducing other elements during the substrate and solvent mixing stage or introducing other elements using sintering aids during the sintering stage; the coating methods described above include, but are not limited to, coating Li using methods such as ball milling, vapor deposition, or atomic spraying. 7-A PS 6-A X A A coating layer containing other elements is formed on the surface.

[0049] In some embodiments of this application, the cell parameters of the sulfide solid electrolyte are a=b=c=9.84~9.90 Å. The cell parameters of the sulfide solid electrolyte in this application are within the above range, resulting in high ionic conductivity.

[0050] In some embodiments of this application, the ionic conductivity of the sulfide solid electrolyte is ≥5.5 mS / cm. The inventors discovered in their research that the sulfide solid electrolyte of this application has high ionic conductivity, which, when applied to batteries, can improve battery safety, energy density, and low-temperature performance. In this application, the ionic conductivity of the sulfide solid electrolyte ≥5.5 mS / cm refers to the ionic conductivity measured by pressure molding of the sulfide solid electrolyte under 350 MPa pressure.

[0051] In some embodiments of this application, the other elements are selected from at least one of the elements O, Se, F, Mg, Ca, Sr, Zn, Sc, Sb, Si, Ge, Sn, B, Al, Ga, In, Ti, Zr, V, Nb, Cu, Ni, Mn, Cr, Ag, La, Ce, Tb, Te, Pb, As, Bi, Fe, Mo, and Co.

[0052] In some embodiments of this application, the sulfide solid electrolyte is selected from Li doped with other elements. 7-A PS 6-A X A The complex, in which other doping elements are introduced using oxides as raw materials, wherein the oxides are selected from at least one of MgO, CaO, V₂O₅, MnO₂, Fe₂O₃, CoO, NiO, CuO, ZnO, ZrO₂, MoO₃, Ag₂O, SrO, TiO₂, Cr₂O₃, CeO₂, and PbO. Li₂ doped with the above oxides... 7-A PS 6-A X A The composite material can improve ionic conductivity, air stability, and interfacial stability. Li doped with other elements was prepared using the above doping method. 7-A PS 6-A X A The complex, wherein the mass ratio of substrate to oxide can be 99.99:0.01 to 95:5.

[0053] The second aspect of this application provides a chemical formula of Li provided in the first aspect of this application. 7-A PS 6-A X A The method for preparing the compound includes:

[0054] Under an inert atmosphere, the substrate and solvent are mixed and mechanically stirred to obtain a suspension; wherein the substrate includes Li₂S, P₂S₅, and LiX, where X is a halogen; before mixing with the solvent, the substrate is pulverized to a particle size of 3 μm < D₅₀ < 30 μm; 40 μm < D₉₁ < 80 μm; preferably 8 μm < D₅₀ < 20 μm, 50 μm < D₉₁ < 65 μm; the molar ratio of Li₂S to P₂S₅ is (3~5):1; the molar ratio of P₂S₅ to LiX is 1:(2~4); the mass ratio of the substrate to the solvent is 1:(2~4); for example, the particle size D₅₀ of the substrate before mixing with the solvent can be 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, etc. The particle size D90 of the pulverized material can be 40μm, 45μm, 50μm, 60μm, 65μm, 70μm, 75μm, 80μm, or any two of these values; the molar ratio of Li2S to P2S5 can be 3:1, 4:1, 5:1, or any two of these values; the molar ratio of P2S5 to LiX can be 1:2, 1:3, 1:4, or any two of these values; the mass ratio of the substrate to the solvent can be 1:2, 1:3, 1:4, or any two of these values. The molar ratio between the substrates is limited to the above range, which can avoid changes in the material structure and thus reduce the ionic conductivity. The mass ratio of the substrate to the solvent is also limited to the above range, which not only reduces production costs but also reduces environmental pollution compared with the traditional liquid phase method. At the same time, by reducing the amount of solvent used, the drying step does not need to be vacuum dried, but can be completed by standing at room temperature and pressure, which not only reduces energy consumption but also reduces production costs.

[0055] Controlling the particle size (D50) of the raw materials for synthesizing sulfide solid electrolytes within the range of 3–30 μm helps to improve the structural uniformity and processability of the substrate while ensuring reactivity. Within this range, the contact area between the raw materials is moderate, promoting the full progress of the solid-phase reaction, resulting in a uniform crystal structure and reducing impurity phase formation. Furthermore, a suitable D50 facilitates effective particle packing during subsequent sintering, improving density, reducing porosity, and thus enhancing ionic conductivity and interfacial stability. If D50 is less than 3 μm, the specific surface area of ​​the substrate powder increases significantly, making it prone to agglomeration during sintering, leading to uneven particle growth and increased structural defects. Conversely, a D50 greater than 30 μm results in incomplete reaction, poor sintering density, and ultimately the formation of residual reactants or weakly bonded regions, reducing the fracture toughness and ionic conductivity of the sulfide solid electrolyte. Therefore, controlling the substrate D50 within the range of 3–30 μm is one of the key process parameters for achieving high-performance sulfide solid electrolytes.

[0056] Building upon controlling D50 to enhance fracture toughness, further controlling the substrate's D99 within the range of 40–80 μm can improve the overall uniformity and formability of the particle system, thereby optimizing the sintering densification process and enhancing the mechanical properties of the finished product. This upper limit of D99 avoids the presence of too many ultra-large particles (>80 μm) in the system. Such particles are prone to causing local voids or stress concentrations during compaction, forming defect areas after sintering and thus weakening fracture toughness. Simultaneously, the lower limit of D99 (>40 μm) also avoids the problems of excessively narrow particle size distribution and insufficient system fluidity, contributing to more uniform stress transmission and a denser packing structure during pressing. Therefore, controlling the substrate's D99 within the scope of this application can further improve the fracture toughness and ionic conductivity of sulfide solid electrolytes.

[0057] In this application, a process strategy of finely controlling the particle size of raw materials was adopted to optimize the mechanical properties of sulfide solid electrolytes, particularly the effective control of fracture toughness. Specifically, the lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium halides (such as LiCl and LiBr) used were all pulverized to a D50 range of 3–30 μm and a D99 range of 40–80 μm. This particle size distribution differs from that of commercially available conventional raw materials and is an unconventional particle size design. Lithium sulfide is often supplied in granular or agglomerated form, with a marketable particle size D50 of 50–200 μm and D99 exceeding 250 μm. Phosphorus pentasulfide, on the other hand, is mainly in the form of obvious flakes or lumps, with industrial-grade particle sizes D50 mostly above 100 μm and D99 reaching above 200 μm. Not only are the particle sizes large, but they are also prone to uneven aggregation, making it difficult to form a uniform mixing system. Lithium halides such as LiCl and LiBr are often large particles or crystalline powders, with particle sizes generally exceeding 100 μm. They contain a certain proportion of large particles (D99>150 μm) and are prone to hygroscopic agglomeration, further affecting dispersion uniformity and reactivity.

[0058] By refining the aforementioned raw materials to a D50 range of 3–30 μm and a D99 range of 40–80 μm, the packing state and sintering densification process of the particle system were optimized, significantly improving the mechanical strength, especially fracture toughness, of the material. Controlling the D50 ensures that the main particles in the system are within a suitable size range, possessing good compaction and reactivity. During compaction, a moderate median particle size facilitates uniform contact between particles, increasing the initial packing density and providing a dense and continuous structural foundation for subsequent sintering. Simultaneously, a higher specific surface area promotes rapid growth and densification of the sintering neck, reducing porosity and enhancing the overall structural strength of the material. Adjusting the D99 plays a crucial role in constraining the extreme values ​​of particle distribution in the system, ensuring that the upper limit of particle distribution remains within a reasonable range. Limiting the maximum particle size helps avoid excessive size differences between particles, thus promoting a more structurally stable packing pattern in the entire particle system. During compaction, this controlled distribution facilitates uniform stress transfer, avoiding localized stress concentration, thereby improving the overall consistency of the compacted structure. During sintering, the controlled maximum particle size helps to form a continuous and non-abrupt dense phase, increasing the complexity of crack propagation paths and thus improving fracture toughness.

[0059] Furthermore, if the raw materials are pulverized simultaneously, reactions may occur between them during pulverization, leading to uneven reactions in the subsequent preparation of the sulfide solid electrolyte. This, in turn, affects the purity, fracture toughness, and ionic conductivity of the sulfide solid electrolyte. Compared to simultaneous pulverization, pulverizing the raw materials separately avoids reactions between them during pulverization, allowing for a more thorough and uniform solid-phase reaction in the subsequent preparation of the sulfide solid electrolyte. This, in turn, improves the fracture toughness and ionic conductivity of the sulfide solid electrolyte.

[0060] In summary, by separately crushing the substrate and controlling the substrate particle sizes D50 and D99 within the scope of this application, D50 control provides uniform compaction and sintering drive, while D99 control suppresses potential weak areas in the structure. The synergistic effect of the two results in the final electrolyte material having better compactness and fracture toughness, meeting the comprehensive requirements of high-performance solid-state batteries for structural stability and mechanical strength.

[0061] In this application, the method for pulverizing the substrate can be at least one of mechanical pulverization, ball milling, and air jet milling. This application does not specifically limit the pulverization method, as long as it meets the purpose of this application.

[0062] The suspension was allowed to stand at room temperature and pressure to allow the solvent to evaporate, yielding Li. 7-A PS 6-A X A Precursor mixture; The preparation method of this application selects static drying at room temperature and pressure. Compared with other drying methods such as heating and vacuum drying, it can reduce the amount of solvent that evaporates simultaneously and forms cavities in the mixture, thereby further improving the ionic conductivity and fracture toughness of the sulfide solid electrolyte.

[0063] The Li 7-A PS 6-A X A The precursor mixture was sintered to obtain Li 7-A PS 6-A X AThe sintering process includes a first sintering and a second sintering. The first sintering temperature is 150-300℃, and the time is 1-6 hours; preferably, the temperature is 150-200℃, and the time is 3-6 hours. The second sintering temperature is 450-600℃, and the time is 5-10 hours; preferably, the temperature is 550-600℃, and the time is 5-7 hours. For example, the temperature of the first sintering can be 150℃, 200℃, 250℃, 300℃, or any two of these values, and the time can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, or any two of these values. The temperature of the second sintering can be 450℃, 500℃, 550℃, 600℃, or any two of these values, and the time can be 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, or any two of these values. The inventors discovered in their research that during sintering, the substrate begins to react. When the sintering temperature and time are below the range of this application, the substrate does not react completely, and some halide ions (such as chloride ions) are not incorporated into the product's unit cell. This results in a smaller unit cell parameter, lower ionic conductivity, and a large number of micropore defects inside the sample, leading to increased brittleness. Adjusting the sintering temperature and time within the range of this application not only helps to improve the material's density and reduce porosity, thereby enhancing fracture toughness, but also allows the substrate to react completely, with halide ions (such as chloride ions) being largely incorporated into the unit cell. This results in a suitable increase in unit cell parameter and higher ionic conductivity. At the same time, using the sintering method of this application can effectively reduce the residual organic solvent in the sulfide solid electrolyte, alleviate carbonization, and thus improve the ionic conductivity and overall performance of the sulfide solid electrolyte.

[0064] In some embodiments of this application, the heating rate of the first sintering is 2~7℃ / min; the heating rate of the second sintering is 5~12℃ / min. For example, the heating rate of the first sintering can be 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, or a range of any two of these values; the heating rate of the second sintering can be 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min, 11℃ / min, 12℃ / min, or a range of any two of these values. Limiting the heating rates of the two sintering processes within the above ranges in this application ensures that solvent evaporation does not introduce excessive voids into the sulfide solid electrolyte, and that the sulfide solid electrolyte maintains a complete crystal structure, thereby improving its fracture toughness, purity, and ionic conductivity.

[0065] The purpose of the first sintering is to remove residual solvent from the system while preventing the introduction of large cavities into the product due to rapid solvent evaporation. The heating rate needs to be maintained at 2~7℃ / min. Too high a heating rate will cause the solvent to evaporate too quickly and introduce cavities; too low a heating rate will result in excessively long heating times, increasing labor and energy consumption. The purpose of the second sintering is to form the silver-germanium sulfide crystal form, thereby obtaining a sulfide product with high ionic conductivity. The heating rate needs to be maintained at 5~12℃ / min. Too high a heating rate can easily damage the heating equipment and cause runaway heating, leading to uneven heating. Too low a heating rate will cause some phosphorus pentasulfide to decompose before the raw materials begin to react and form the target crystal form, producing gases that cannot act on the final product, resulting in a product with an unsuitable elemental ratio.

[0066] In this application, the method for controlling the heating rate is not particularly limited, as long as it can achieve the purpose of this application. For example, the heating rate can be set by the heating program of the sintering furnace. This application does not particularly limit the selection of the sintering furnace. For example, a tube furnace with model NBD-T1500-100T2GF can be selected.

[0067] In this application, the inert atmosphere is not specifically limited, as long as it can achieve the purpose of this application. For example, the inert atmosphere is selected from, but not limited to, at least one of argon and nitrogen.

[0068] In this application, the halogen is at least one of Cl, Br and I.

[0069] In this application, the conditions for the suspension to stand are not particularly limited, as long as they can achieve the purpose of this application. For example, under the protection of an inert atmosphere, the suspension is left to stand overnight at room temperature and normal pressure to allow the solvent to evaporate and the residual solvent content is kept below 5 wt%.

[0070] In one embodiment of this application, the solvent is selected from at least one of n-hexane, benzene, toluene, cyclohexane, n-pentane, cyclopentane, n-heptane, and dimethyl carbonate. The inventors have discovered that using the solvent of this application not only facilitates the thorough dispersion and mixing of substrate particles, resulting in a precursor powder with uniform particles and a dense structure, thereby improving the fracture toughness of the sulfide solid electrolyte, but also effectively prevents the hydrolysis of the precursor, reducing the content of oxygen impurities (such as Li3PO4) in the sulfide solid electrolyte, thereby improving the purity and ionic conductivity of the sulfide solid electrolyte and enhancing its high efficiency and stability in applications.

[0071] In this application, the solvent used is an inert solvent that does not chemically react with the reaction substrate. This type of solvent is chemically stable, has low polarity, and does not participate in the complexation, alcoholysis, or redox processes in the reaction system. It provides a good dispersion environment during the physical mixing stage and completely evaporates during subsequent drying and heat treatment, leaving no carbon source or byproducts, thus ensuring the purity and structural homogeneity of the final product. In contrast, alcohols (such as anhydrous ethanol and isopropanol) or other polar solvents widely used in the prior art, while possessing strong dissolving or wetting abilities, often cause side reactions, such as alcoholysis or complexation, when processing reactive substrates (such as lithium sulfide and phosphorus pentasulfide), leading to an imbalance in the precursor component ratio or the formation of intermediate products that are difficult to remove. Furthermore, residual organic functional groups in polar solvents are easily carbonized during heat treatment, increasing the carbon impurity content in the final sulfide solid electrolyte, affecting ionic conductivity and interfacial stability, and even reducing the fracture toughness of the material.

[0072] In one embodiment of this application, mechanical stirring is carried out at room temperature and pressure, the stirring speed is 300 rpm to 600 rpm, and the stirring time is 12 to 24 hours. For example, the stirring speed can be 300 rpm, 350 rpm, 400 rpm, 480 rpm, 520 rpm, 600 rpm, or any combination of two of these values; the stirring time can be 12 hours, 15 hours, 20 hours, 24 hours, or any combination of two of these values. By controlling the mixing method of the substrate and solvent, and the temperature, pressure, and stirring speed within the above ranges, reactions between the substrates can be avoided during stirring, ensuring that a sufficient and uniform solid-phase reaction occurs only during the sintering stage. This is beneficial for the preparation of sulfide solid electrolytes, improving the purity, overall density, and microstructure uniformity of the sulfide solid electrolytes, thereby improving the fracture toughness and ionic conductivity of the sulfide solid electrolytes. When other mixing methods are used (such as ultrasonic dispersion), mechanical stirring under high temperature and pressure, or excessively high rotation speeds (e.g., greater than 600 rpm), reactions may occur between the substrates, leading to uneven reaction in the subsequent preparation of the sulfide solid electrolyte, which in turn affects the purity, fracture toughness, and ionic conductivity of the sulfide solid electrolyte. Furthermore, limiting the stirring time within the aforementioned range in this application allows for more thorough substrate contact, resulting in larger cell parameters and reduced interparticle porosity, thereby achieving higher ionic conductivity and fracture toughness. In summary, by controlling the mixing of the substrate and solvent through mechanical stirring, and by controlling the mechanical stirring conditions within the aforementioned range, a sulfide solid electrolyte with high purity and good fracture toughness and ionic conductivity can be prepared.

[0073] In one embodiment of this application, the solvent evaporation rate is 1.5~7.0 mg / cm³. 2•h. For example, the solvent evaporation rate can be 1.5 mg / cm³. 2 ·h, 3 mg / cm 2 ·h, 4.5 mg / cm 2 ·h、6 mg / cm 2 ·h, 7.0 mg / cm 2 •h can be a range consisting of any two of these values. The inventors discovered in their research that limiting the solvent evaporation rate within the above range in this application can prevent a large amount of solvent from evaporating simultaneously in the mixture and forming cavities, thereby further improving the ionic conductivity and fracture toughness of the sulfide solid electrolyte.

[0074] This application does not impose any particular limitation on the method for controlling the solvent evaporation rate, as long as it achieves the purpose of this application. For example, in a room temperature and atmospheric pressure environment, by using different evaporation containers, the Li... 7-A PS 6-A X A The thickness of the precursor mixture is controlled at 1~5mm, and per gram of Li 7-A PS 6-A X A The dry specific surface area of ​​the precursor mixture is controlled at 1.5~3 cm². 2 The rate of solvent evaporation is controlled, and the thickness and specific surface area can be obtained by measuring from the outside of the container.

[0075] In this application, Li 7-A PS 6-A X A After the precursor mixture has volatilized for t hours, the Li before and after volatilization was determined by weighing. 7-A PS 6-A X A The masses of the precursor mixture are m0 and m1. The amount of solvent evaporated during the evaporation time is m0 minus m1. Dividing this by the evaporation time t and the dry specific surface area S gives the solvent evaporation rate v, v = (m0 - m1) / (t × S).

[0076] In summary, by separately pulverizing the substrate, controlling the D50 and D99 of the substrate, using an inert solvent within the scope of this application, and adjusting the stirring conditions, stirring speed, and stirring time when mixing the substrate and solvent, it is possible to control the substrate from reacting before the first sintering. If the substrate partially reacts before sintering, it will lead to an uneven reaction process, weak interfacial bonding between product particles, and the formation of a porous, non-dense structure, thereby reducing the mechanical integrity and fracture toughness of the material. This invention, by inhibiting the premature reaction of the substrate, ensures that the raw materials undergo a full and uniform solid-phase reaction during the heating and sintering stage, which helps to achieve the gradual formation of a dense structure during the sintering process, enhances the bonding strength and interfacial compatibility between particles, and improves the overall density and microstructure uniformity of the sulfide solid electrolyte, thereby improving the fracture toughness and ionic conductivity of the sulfide solid electrolyte.

[0077] In one embodiment of this application, post-processing is required after sintering, and the post-processing includes pulverization. This application does not particularly limit the specific implementation of the pulverization method, as long as it achieves the purpose of this application. For example, grinding, mechanical pulverization, and high-energy ball milling can be used for pulverization.

[0078] In this application, Li doped with other elements is prepared. 7-A PS 6-A X A The methods for preparing the complex include, but are not limited to, those described above for preparing Li 7-A PS 6-A X A Based on this, other elements are introduced during the substrate-solvent mixing stage or as sintering aids during the sintering stage; Li coated with other elements is prepared. 7-A PS 6-A X A The composite includes, but is not limited to, the Li prepared above prepared by methods such as ball milling, vapor deposition, or atomic spraying. 7-A PS 6-A X A A coating layer containing other elements forms on the surface. Therefore, the above-mentioned Li... 7-A PS 6-A X A The technical effects brought about by the preparation parameters are also applicable to Li coated or doped with other elements. 7- A PS 6-A X A Complex.

[0079] A third aspect of this application provides a battery comprising a positive electrode, a negative electrode, and the sulfide solid electrolyte described in the first aspect of this application. Applying the sulfide solid electrolyte of this application to a battery significantly improves the battery's safety, energy density, and low-temperature performance.

[0080] This application does not impose any special limitations on the positive and negative electrode plates in the battery, as long as they can achieve the purpose of this application.

[0081] The fourth aspect of this application provides the application of the battery described in the third aspect of this application in electric vertical takeoff and landing (EVTOL) aircraft, especially in low-altitude economical manned EVTOL aircraft, which can improve the flight endurance, safety performance and extreme environment resistance of the spacecraft, while the long-life battery can reduce the maintenance frequency and cost of the aircraft.

[0082] Example

[0083] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Unless otherwise specified, "parts" and "%" are based on mass, "room temperature" is 25±5℃, "atmospheric pressure" is 101kPa, and "overnight" is 12~24h.

[0084] Test methods and equipment:

[0085] Ion conductivity test

[0086] In an argon-filled glove box, 100 mg of solid electrolyte powder was weighed and placed in a molded battery (Wuhan Chuangneng CN-01) with stainless steel sheets at both ends, each with a diameter of 9 mm. The battery was then pressurized at 200 MPa or 350 MPa, with the electrolyte sheet thickness being 1 mm. AC impedance spectroscopy was performed using the molded battery. Electrochemical impedance spectroscopy (EIS) was used to determine the electrolyte impedance. On an electrochemical workstation (ChenHua, CHI630E), a DC polarization voltage of 1 V was applied to measure the impedance, with an amplitude of 50 mV and a frequency range of 1 Hz to 10 MHz. The ionic conductivity of the electrolyte material was calculated using the following formula:

[0087]

[0088] Where σ is the ionic conductivity, in units of S cm. –1 L is the thickness of the electrolyte sheet, in cm; R is the electrolyte resistance, in Ω; S is the effective contact area between the stainless steel sheet and the electrolyte powder, in cm². 2 .

[0089] X-ray powder diffraction test

[0090] X-ray powder diffraction (XRD) was used to analyze the crystal structure of the samples. A Bruker D8 Advance diffractometer equipped with Cu Kα radiation (λ = 1.5406 Å) as the light source was employed. The test parameters were set as follows: tube voltage 40 kV, tube current 40 mA, scanning range 2θ = 5°–90°, scanning step size 0.02°, and scanning rate 5° / min. The samples were uniformly dispersed as powder on a glass slide without a diffraction background, and compaction was performed to reduce the influence of interparticle voids on the diffraction results.

[0091] The XRD data were processed and analyzed using Jade software. First, the raw data was imported into the software, and after background subtraction and signal optimization, it was exported as a text file. The text file was then imported into the refinement software FullProf. An initial model was built based on the known crystal structure of the sample, with preliminary unit cell parameters and space group input. Instrument parameters such as zero-point offset and sample displacement were adjusted to complete the initial fitting.

[0092] During the refinement process, peak shape parameters (such as peak width and peak shape factor), background functions, cell parameters (a, b, c, α, β, γ), and atomic positions and occupancy are gradually optimized to achieve final convergence of the fit. The fitting results are evaluated based on the goodness of fit Chi2, while the residual spectrum is used to determine the quality of the fit. Once the refinement results converge (Chi2 < 3), the cell parameters a, b, and c can be obtained from the software's output text.

[0093] Test methods for fracture toughness

[0094] 80 mg of sulfide solid electrolyte powder was weighed in a glove box and placed into a rectangular mold (25 mm × 2.5 mm × 2 mm). The mold was then cold-pressed at 200 MPa for 1 min to obtain a dense bulk sample. The sample was mechanically polished to a smooth surface. To guide crack initiation, a single-sided rectangular notch was machined at the center of the tensile side of the sample using a wire EDM machine. The notch was approximately 0.2 mm wide and 1 mm deep, with the notch facing upwards at the center of the span to ensure crack propagation along the notch direction. Fracture toughness testing was performed using the three-point bending method on an Instron 5944 electronic universal testing machine equipped with a 5 kN force sensor. The test was conducted in a dry air atmosphere at a temperature of 25 ± 2°C and a relative humidity of <20%. The loading span was set to 20 mm, and the loading rate was 0.05 mm / min. The maximum load Pmax during loading was recorded, and the fracture toughness was calculated using the following formula:

[0095]

[0096] Where S is the loading span, B is the specimen thickness, W is the specimen width, a is the notch depth, and f(a / W) is the geometric correction factor (obtained from a table based on the a / W ratio according to the ASTM C1421 standard method). Each test group should contain no fewer than 5 samples, and the average value should be taken as the final test result.

[0097] Methods for testing substrate particle size:

[0098] Particle size distribution was tested using a Bettersize 2600 laser particle size analyzer. Approximately 0.1 g of sample was weighed, and an appropriate amount of n-octane was added as a dispersion medium. The sample was ultrasonically dispersed for 3 minutes to promote uniform particle dispersion. The dispersed sample was then injected into the instrument's wet circulation chamber, the shading rate was adjusted to 20%, and the circulation system was activated to maintain uniform dispersion before testing began. Each sample was measured three times, and its D50 and D99 particle size parameters were recorded.

[0099] Porosity testing methods:

[0100] The porosity of the sulfide solid electrolyte was determined using mercury porosimetry (MPA) with an AutoPore V 9600 fully automated mercury porosimeter manufactured by Micromeritics, USA. Before testing, the electrolyte was vacuum-dried at room temperature for 12 hours to remove residual solvent. During testing, a vacuum pretreatment to 6.7 Pa (50 mTorr) was performed to fully expel gas from the sample pores. Subsequently, pressure was gradually applied, with a low-pressure range of 0.0036–0.21 MPa (0.5–30 psi) for detecting large pore structures and a high-pressure range of 0.21–414 MPa (30–60,000 psi) for determining small and medium pores. The mercury contact angle was set to 130°, and the surface tension was 485 dyn / cm. Finally, the total pore volume, average pore diameter, and open porosity of the sample were automatically calculated using software.

[0101] Example 1-1

[0102] Li₂S, P₂S₅, and LiCl were ball-milled separately using a Tianchuang Powder QXQM-6 ball mill. After milling, the D₅₀ of Li₂S was 10.4 μm and the D₉₁ was 53.1 μm; the D₅₀ of P₂S₅ was 12.2 μm and the D₉₁ was 56.7 μm; and the D₅₀ of LiCl was 14.1 μm and the D₉₁ was 60.9 μm.

[0103] In an Ar atmosphere, pulverized Li₂S, P₂S₅ and LiCl in a molar ratio of 4:1:3 were weighed as substrates. 1 kg of the above substrates corresponded to 3 L of n-hexane (substrate:solvent mass ratio = 1:2). The mixture was stirred at 500 rpm for 12 h at room temperature and atmospheric pressure to obtain a suspension.

[0104] The suspension was left overnight in an Ar atmosphere at room temperature and atmospheric pressure to allow the solvent to evaporate, with the evaporation rate controlled at 5 mg / cm³. 2 •h, so that the solvent residue is kept below 5wt%, a solid electrolyte precursor mixture is obtained, and its X-ray diffraction pattern is as follows. Figure 4 As shown; the method for controlling the evaporation rate is as follows: at room temperature and atmospheric pressure, a large petri dish is used to achieve a dry specific surface area of ​​1.51 cm² per gram of sample. 2 The sample thickness was 2.2 mm.

[0105] After the solid electrolyte precursor mixture was allowed to stand and dry, it was heated to 200°C for 3 hours at a heating rate of 5°C / min to remove residual organic solvent; then, it was heated to 550°C for 5 hours at a heating rate of 10°C / min to obtain the sulfide solid electrolyte (Li). 5.5 PS 4.5 Cl 1.5 Its X-ray diffraction pattern is as follows: Figure 1 As shown.

[0106] Examples 1-2 to Examples 1-3

[0107] Except for adjusting the type of LiX according to Table 1, the rest is the same as in Example 1-1.

[0108] In Examples 1-2, the D50 of the pulverized LiBr was 12.8 μm and the D99 was 58.0 μm.

[0109] In Examples 1-3, the D50 of the pulverized LiI was 14.6 μm and the D99 was 62.2 μm.

[0110] Examples 1-4 to Examples 1-5

[0111] Except for adjusting the molar ratio of the substrate according to Table 1, the rest is the same as in Example 1-1.

[0112] Examples 1-6 to Examples 1-7

[0113] Except for adjusting the mass ratio of substrate to solvent according to Table 1, the rest is the same as in Examples 1-1.

[0114] Examples 1-8 to Examples 1-9

[0115] Except for adjusting the first sintering temperature according to Table 1, the rest is the same as in Example 1-1.

[0116] Examples 1-10 to Examples 1-11

[0117] Except for adjusting the first sintering time according to Table 1, the rest is the same as in Example 1-1.

[0118] Examples 1-12 to Examples 1-13

[0119] Except for adjusting the second sintering temperature according to Table 1, the rest is the same as in Example 1-1.

[0120] Examples 1-14 to Examples 1-15

[0121] Except for adjusting the second sintering time according to Table 1, the rest is the same as in Examples 1-1. The X-ray diffraction patterns of Examples 1-15 are as follows: Figure 2 As shown.

[0122] Examples 1-16

[0123] Except for adjusting the type of LiX and the molar ratio of the substrate according to Table 1, the rest is the same as in Example 1-1.

[0124] The D50 of pulverized LiCl was 14.1 μm and the D99 was 60.9 μm, while the D50 of pulverized LiBr was 12.8 μm and the D99 was 58.0 μm.

[0125] Examples 2-1 to 2-4

[0126] Except for adjusting the D50 and D99 of Li2S, P2S5 and LiCl after pulverization according to Table 2, the rest is the same as in Example 1-1.

[0127] Examples 3-1 to 3-6

[0128] Except for adjusting the type of solvent according to Table 3, the rest is the same as in Examples 1-1.

[0129] Examples 4-1 to 4-4

[0130] Except for adjusting the first sintering heating rate according to Table 4, the rest is the same as in Example 1-1.

[0131] Examples 4-5 to Examples 4-8

[0132] Except for adjusting the second sintering heating rate according to Table 4, the rest is the same as in Example 1-1.

[0133] Examples 5-1 to 5-6

[0134] Except for adjusting the stirring time according to Table 5, everything else is the same as in Example 1-1.

[0135] Examples 6-1 to 6-2

[0136] Except for adjusting the post-processing method according to Table 6, the rest is the same as in Example 1-1.

[0137] Example 7-1

[0138] Except for adjusting the molar ratio of the pulverized substrates Li2S, P2S5, and LiCl to 5:1:2, the mass ratio of the substrate to the solvent dimethyl carbonate to 1:4, the second sintering time to 4 hours, and the resulting sulfide solid electrolyte to be Li6PS5Cl, everything else is the same as in Example 1-1.

[0139] Example 8-1

[0140] Besides adjusting the raw material ratio to a molar ratio of 3.8:1:3:0.1 for pulverized Li₂S, P₂S₅, LiCl, and SiO₂ (D₅₀ = 14.9 μm, D₹₁ = 58.2 μm), the resulting sulfide solid electrolyte is Li 5.3 PSi 0.05 S 4.4 O 0.1 Cl 1.5 Except for the above, the rest is the same as in Example 1-1.

[0141] Example 8-2

[0142] Besides adjusting the raw material ratio to a molar ratio of 3.8:1:3:0.1 for pulverized Li₂S, P₂S₅, LiCl, and ZrO₂ (D₅₀ = 11.3 μm, D₉₁ = 52.1 μm), the resulting sulfide solid electrolyte is Li 5.3 PZr 0.05 S 4.4 O 0.1 Cl 1.5 Except for the above, the rest is the same as in Example 1-1.

[0143] Comparative Examples 1-1 to 1-2

[0144] Except for adjusting the molar ratio of the substrate according to Table 1, everything else was the same as in Example 1-1. The X-ray diffraction pattern of Comparative Example 1-1 is shown below. Figure 3 As shown.

[0145] Comparative Examples 1-3 to 1-4

[0146] Except for adjusting the mass ratio of substrate to solvent according to Table 1, the rest is the same as in Examples 1-1.

[0147] Comparative Examples 1-5

[0148] Except for not performing the first sintering, it is the same as in Example 1-1.

[0149] Comparative Examples 1-6 to 1-7

[0150] Except for adjusting the first sintering temperature and time according to Table 1, the rest is the same as in Example 1-1.

[0151] Comparative Examples 1-8 to 1-9

[0152] Except for adjusting the second sintering temperature and time according to Table 1, the rest is the same as in Example 1-1.

[0153] Comparative Example 2-1

[0154] Except for the use of ball milling when mixing the substrate and solvent, the process was the same as in Examples 1-1. Zirconium balls were used for ball milling at a ball-to-solvent ratio of 5:1, and the mixture was milled at 300 rpm for 12 hours. The X-ray diffraction pattern of the solid electrolyte precursor mixture in Comparative Example 2-1 is shown below. Figure 5 As shown.

[0155] Comparative Example 2-2

[0156] Except for the use of ultrasonic dispersion when mixing the substrate and solvent, the process was the same as in Example 1-1. The ultrasonic treatment frequency was once every 2 hours, the ultrasonic power was 800 W, and the ultrasonic time was 5 minutes per treatment. The X-ray diffraction pattern of the solid electrolyte precursor mixture in Comparative Example 2-2 is shown below. Figure 6 As shown.

[0157] Comparative Example 3-1

[0158] Except for drying the suspension under vacuum at 60°C for 24 hours instead of leaving it overnight at room temperature and atmospheric pressure in an Ar atmosphere, the rest is the same as in Example 7-1.

[0159] Comparative Example 3-2

[0160] Using Example 2 from the published text of patent application CN115621538A as Comparative Example 3-2, the X-ray diffraction pattern of its electrolyte precursor powder is as follows: Figure 7 As shown.

[0161] Comparative Example 4-1

[0162] Except for changing the solvent to the polar solvent ethanol, everything else is the same as in Examples 1-1.

[0163] When using ethanol as a solvent, the strong interaction between the substrate and the ethanol solvent causes the substrate to dissolve or even form a complex. Therefore, the ethanol cannot be dried, making subsequent experiments impossible, and no relevant data is available.

[0164] The preparation and performance parameters of each embodiment and comparative example are shown in Tables 1 to 9.

[0165] Table 1

[0166]

[0167] In Table 1, " / " indicates that there are no relevant parameters.

[0168] Table 2

[0169]

[0170] Table 3

[0171]

[0172] Table 4

[0173]

[0174] Table 5

[0175]

[0176] Table 6

[0177]

[0178] Table 7

[0179]

[0180] Table 8

[0181]

[0182] Table 9

[0183]

[0184] As can be seen from Table 1, limiting the molar ratio of the substrate within the range specified in this application can avoid the decrease in fracture toughness and ionic conductivity caused by changes in the structure of the sulfide solid electrolyte material. Limiting the mass ratio of substrate to solvent within the range specified in this application can yield a sulfide solid electrolyte with higher fracture toughness and higher ionic conductivity, and the sulfide solid electrolyte also has high purity. Limiting the two sintering temperatures and times within the range specified in this application not only helps to improve the compactness of the material and reduce porosity, thereby improving fracture toughness, but also allows the substrate to react completely, and halide ions (such as chloride ions) to be basically doped into the unit cell, thereby appropriately increasing the unit cell parameters and increasing the ionic conductivity. When the two sintering temperatures and times exceed the range specified in this application, the substrate does not react completely, and some halide ions (such as chloride ions) are not doped into the unit cell of the product, resulting in a smaller unit cell parameter, lower ionic conductivity, and a large number of micropore defects inside the sample, leading to a decrease in fracture toughness. As shown in Table 2, pulverizing the substrate before mixing it with the solvent, with D50 and D99 within the scope of this application, is beneficial for improving the ionic conductivity and fracture toughness of the sulfide solid electrolyte. Ultrasonic dispersion after mixing the substrate with the solvent, as in Comparative Example 3-2, increases the porosity of the sulfide solid electrolyte, while decreasing its fracture toughness and ionic conductivity. As shown in Table 3, the solvent types within the scope of this application can effectively avoid precursor hydrolysis and reduce the content of oxygen impurities (such as Li3PO4) in the sulfide solid electrolyte, thereby further improving its purity and ionic conductivity. As shown in Table 4, the heating rates of the two sintering processes within the scope of this application ensure that solvent evaporation does not introduce excessive voids into the sulfide solid electrolyte, and that the crystal structure of the sulfide solid electrolyte remains intact, thereby improving its fracture toughness, purity, and ionic conductivity. As shown in Table 5, when mechanical stirring is carried out at room temperature and pressure, and the stirring speed is within the range of this application, no reaction occurs between the substrates when they are mixed with the solvent, resulting in a sulfide solid electrolyte with good fracture toughness and ionic conductivity. Adjusting the stirring time within the range of this application allows for more sufficient substrate contact, appropriately increases the cell parameters, and reduces the porosity between substrate particles, thereby obtaining higher ionic conductivity and fracture toughness. Table 6 shows that the post-treatment method of this application achieves high ionic conductivity and fracture toughness. Table 8 shows that using the static drying method at room temperature and pressure of this application results in low porosity of the sulfide solid electrolyte, leading to high fracture toughness and high ionic conductivity. However, using vacuum drying increases the porosity of the sulfide solid electrolyte, decreasing its fracture toughness and ionic conductivity. Furthermore, using ultrasonic dispersion followed by vacuum drying further increases the porosity of the sulfide solid electrolyte, further decreasing its fracture toughness and ionic conductivity.As can be seen from Table 9, oxide-doped sulfide solid electrolytes can improve ionic conductivity. Figures 4 to 6 It can be seen that in Example 1-1, only the characteristic peaks of the substrate lithium sulfide and lithium chloride (phosphorus pentasulfide has an amorphous structure, and its diffraction peak intensity in XRD is extremely low, thus masked) are observed. However, in Comparative Examples 2-1 and 2-2, the relative intensity of the peaks of the substrate lithium sulfide and lithium chloride decreases, while the relative intensity of the intermediate Li3PS4 and the product LPSC increases. This indicates that a reaction has already occurred between the substrates at this point, meaning that the reaction between the substrates and solvent, achieved through methods such as ball milling or ultrasonic dispersion, has already taken place before sintering. Referring to Table 7, the use of ball milling and ultrasonic dispersion during substrate and solvent mixing indicates that some substrates have already reacted before sintering, leading to a decrease in the purity, fracture toughness, and ionic conductivity of the final sulfide solid electrolyte. Figure 4 and Figure 7 It can also be seen that in Comparative Example 3-2, a reaction had already occurred between the substrates before sintering, leading to a decrease in the purity of the sulfide solid electrolyte. This indicates that the mechanism published in patent application CN115621538A is completely different from the mechanism of this application. Furthermore, from... Figures 1 to 3 It can be seen that the preparation method of this application can successfully prepare sulfide solid electrolytes. In summary, the sulfide solid electrolyte of this application has high fracture toughness and high ionic conductivity. Furthermore, the preparation method of this application reduces the amount of solvent used, thereby reducing the emission of organic waste gas and the burden of solvent treatment during the production process; moreover, by reducing the amount of solvent used, the drying step does not need to be vacuum dried, but can be completed by standing at room temperature and pressure, which not only reduces energy consumption but also lowers production costs. At the same time, the combination of drying and sintering processes further simplifies the process flow and improves production efficiency. In addition, the multi-step sintering method of this application effectively reduces the residual organic solvent in the electrolyte, alleviates the carbonization phenomenon that may occur in the subsequent sintering process, and ensures the high purity and uniformity of the electrolyte powder by controlling the sintering temperature and time within the range of this application. Furthermore, batteries containing the sulfide solid electrolyte of this application or the sulfide solid electrolyte prepared by the preparation method of this application have high safety and energy density as well as good low-temperature performance, and can be applied to electric vertical take-off and landing aircraft, such as low-altitude economical manned electric vertical take-off and landing aircraft.

[0185] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.

Claims

1. A sulfide solid electrolyte, wherein the sulfide solid electrolyte is selected from the group with the chemical formula Li 7-A PS 6-A X A A compound, wherein X is a halogen, 1 ≤ A ≤ 2; characterized in that, The sulfide solid electrolyte was press-formed into sheets using the ASTM C1421 standard method under a pressure of 200 MPa, and the measured fracture toughness was 0.5-2 MPa m. 1 / 2 .

2. The sulfide solid electrolyte according to claim 1, characterized in that, The sulfide solid electrolyte has cell parameters a=b=c=9.84~9.90Å.

3. The sulfide solid electrolyte according to claim 1, characterized in that, The ionic conductivity of the sulfide solid electrolyte is ≥5.5 mS / cm.

4. The sulfide solid electrolyte according to claim 1, characterized in that, The sulfide solid electrolyte further includes at least one of the following elements: O, Se, F, Mg, Ca, Sr, Zn, Sc, Sb, Si, Ge, Sn, B, Al, Ga, In, Ti, Zr, V, Nb, Cu, Ni, Mn, Cr, Ag, La, Ce, Tb, Te, Pb, As, Bi, Fe, Mo, and Co, which are introduced by doping or coating.

5. The sulfide solid electrolyte according to claim 1, characterized in that, The sulfide solid electrolyte is doped with an oxide, which is selected from at least one of MgO, CaO, V2O5, MnO2, Fe2O3, CoO, NiO, CuO, ZnO, ZrO2, MoO3, Ag2O, SrO, TiO2, Cr2O3, CeO2, and PbO.

6. A method for preparing a sulfide solid electrolyte according to any one of claims 1 to 5, characterized in that, The preparation method of the sulfide solid electrolyte includes the method for preparing the electrolyte with the chemical formula Li 7-A PS 6-A X A A method for preparing a compound, wherein the chemical formula is Li 7-A PS 6-A X A The methods for preparing the compounds include: Under an inert atmosphere, the substrate and solvent are mixed and mechanically stirred to obtain a suspension; wherein the substrate includes Li2S, P2S5 and LiX, where X is a halogen; before mixing the substrate and solvent, the substrate is pulverized to a particle size of 3um < D50 < 30um and 40um < D99 < 80um. The molar ratio of Li2S to P2S5 is (3~5):1; the molar ratio of P2S5 to LiX is 1:(2~4); the mass ratio of the substrate to the solvent is 1:(2~4). The suspension was allowed to stand at room temperature and pressure to allow the solvent to evaporate, yielding Li. 7-A PS 6-A X A Precursor mixture; The Li 7-A PS 6-A X A The precursor mixture was sintered to obtain Li 7-A PS 6-A X A The sintering process includes a first sintering and a second sintering. The temperature of the first sintering is 150~300℃ and the time is 1~6h. The temperature of the second sintering is 450~600℃ and the time is 5~10h.

7. The preparation method according to claim 6, characterized in that, Before mixing the substrate with the solvent, the substrate is pulverized to a particle size of 8µm < D50 < 20µm and 50µm < D99 < 65µm.

8. The preparation method according to claim 6, characterized in that, The first sintering temperature is 150~200℃ and the time is 3~6h; the second sintering temperature is 550~600℃ and the time is 5~7h.

9. The preparation method according to claim 6, characterized in that, The heating rate for the first sintering is 2~7℃ / min; the heating rate for the second sintering is 5~12℃ / min.

10. The preparation method according to claim 6, characterized in that, The solvent is selected from at least one of n-hexane, benzene, toluene, cyclohexane, n-pentane, cyclopentane, n-heptane, and dimethyl carbonate.

11. The preparation method according to claim 6, characterized in that, The mechanical stirring is carried out at normal temperature and pressure, the mechanical stirring speed is 300 rpm to 600 rpm, and the mechanical stirring time is 12 to 24 hours.

12. The preparation method according to claim 6, characterized in that, The solvent evaporates at a rate of 1.5–7.0 mg / cm³. 2 ·h.

13. The preparation method according to claim 6, characterized in that, The sintering process requires post-processing, which includes crushing.

14. A battery, characterized in that, It includes a positive electrode, a negative electrode, and a sulfide solid electrolyte as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Solid state composite electrolyte comprising aramid polymer fibrils

    CN115398734A

  • Sulfide solid electrolyte and preparation method and application thereof

    CN118712466A

Cited By

  • Small-particle-size sulfide solid electrolyte material and preparation method and application thereof

    CN122158683A